2012
DOI: 10.1371/journal.pone.0050665
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of Lexical and Sub-Lexical Reading Processes in the Left Perisylvian Cortex

Abstract: A fundamental issue in cognitive neuroscience is the existence of two major, sub-lexical and lexical, reading processes and their possible segregation in the left posterior perisylvian cortex. Using cortical electrostimulation mapping, we identified the cortical areas involved on reading either orthographically irregular words (lexical, “direct” process) or pronounceable pseudowords (sublexical, “indirect” process) in 14 right-handed neurosurgical patients while video-recording behavioral effects. Intraoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 41 publications
2
26
0
1
Order By: Relevance
“…Electrostimulation of some areas in this gyrus showed that phonological lexical representations could also be affected in isolation, without semantic interferences, as already suggested in previous studies focusing not on auditory tasks but on word reading(Simos, Breier, Fletcher, Foorman & Castillo, 2002;Roux, Durand, Jucla, Rehault, Reddy & Demonet 2012). In the naming process, this region would harbour the neural populations that support the phonological output component of naming, just upstream of the involvement of the articulatory functional areas in the Rolandic region needed to pronounce the target word.In conclusion, these findings are in line with the current conceptualizations of the neural correlates of speech comprehension.…”
supporting
confidence: 69%
“…Electrostimulation of some areas in this gyrus showed that phonological lexical representations could also be affected in isolation, without semantic interferences, as already suggested in previous studies focusing not on auditory tasks but on word reading(Simos, Breier, Fletcher, Foorman & Castillo, 2002;Roux, Durand, Jucla, Rehault, Reddy & Demonet 2012). In the naming process, this region would harbour the neural populations that support the phonological output component of naming, just upstream of the involvement of the articulatory functional areas in the Rolandic region needed to pronounce the target word.In conclusion, these findings are in line with the current conceptualizations of the neural correlates of speech comprehension.…”
supporting
confidence: 69%
“…It is associated with both phonological agraphia, a writing disturbance characterized by an inability to write pseudowords (Alexander et al, 1992b) and phonological dyslexia, i.e., the associated deficit in reading (Beauvois and Derouesne, 1979). Specific pseudoword reading disturbances have recently been observed with direct cortical stimulation of the SMG (Roux et al, 2012). Moreover, the phonological processes supported by the left perisylvian region are believed to be modality-independent and shared between reading and spelling abilities (Rapcsak et al, 2009).…”
Section: Left Smg and Agmentioning
confidence: 99%
“…Regular and unfamiliar word or non-word reading may preferentially rely on phonological pathways, where each grapheme is sequentially mapped to its corresponding phoneme. Neural correlates of phonological processing have most commonly been identified within superior temporal (Graves, Grabowski, Mehta, & Gupta, 2008;Jobard et al, 2003), supramarginal (Graves et al, 2008;Jobard et al, 2003;Roux et al, 2012), insular (Binder et al, 2005;Fiez, Balota, Raichle, & Petersen, 1999;Herbster, Mintun, Nebes, & Becker, 1997) and inferior frontal regions/pars opercularis; BA44; e.g. Jobard et al, 2003;Nixon, Lazarova, Hodinott-Hill, Gough, & Passingham, 2004;Binder et al, 2005).…”
Section: Introductionmentioning
confidence: 99%